Assessment of Dam Operation Impacts on Downstream Surface Hydrology: The Case of Fincha’a-Amarti Hydroelectric Project - Abdurazak Fuad; Adeba Dereje (Journal of Water, 2023)
Dams are built to produce electricity, store water for irrigation, control flood hazards and other uses. The operation of dam has a complicated problem, which includes multiple decision variables, several conflicting and contradictory objectives together with significant uncertainty and risk. The objective of this study was to make an impact assessment that Fincha’a-Amarti dam operation can bring on the downstream activity. Fincha’a-Amarti dam downstream irrigation water requirement was done by using CROPWAT software. The SWAT model was also used to model the watershed and simulate the flow. Meteorological data and spatial data of the study area were used as an input of the model. The meteorological stations considered were Shambu, Fincha’a, Homi, Nashe and Harato. The study shows that downstream water requirement greater than the existing downstream water release during the months of: January, February, March, April, May, September, October, November and December; but existing water release is greater than downstream water requirement during wet season only. Therefore, the study concludes that there is downstream water stress except during wet season.
Keywords: Hydroelectric project